2010
DOI: 10.1111/j.1651-2227.2009.01547.x
|View full text |Cite
|
Sign up to set email alerts
|

Treatment of neonatal abstinence syndrome with clonidine and chloral hydrate

Abstract: This study suggests that a treatment of neonatal abstinence syndrome with clonidine in omission of opiates is possible without causing short-term adverse cardiovascular effects. Considering the retrospective design of the study, controlled and prospective trials are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0
1

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 40 publications
(24 citation statements)
references
References 13 publications
0
23
0
1
Order By: Relevance
“…In a retrospective case series, infants who had evidence of NAS attributable to antenatal methadone exposure had lower severity scores and required fewer days of drug therapy and hospitalization if they had been treated with a combination of clonidine and chloral hydrate rather than a combination of morphine and phenobarbital. 135 A recently published case series from France that used a historical cohort for a comparison has suggested that the treatment of NAS with the phenothiazine, chlorpromazine, as a single drug may be more effective than treatment with morphine. 136 Infants treated with oral morphine had significantly longer median durations of treatment and hospitalization in comparison with infants treated with chlorpromazine.…”
Section: 119-121mentioning
confidence: 99%
“…In a retrospective case series, infants who had evidence of NAS attributable to antenatal methadone exposure had lower severity scores and required fewer days of drug therapy and hospitalization if they had been treated with a combination of clonidine and chloral hydrate rather than a combination of morphine and phenobarbital. 135 A recently published case series from France that used a historical cohort for a comparison has suggested that the treatment of NAS with the phenothiazine, chlorpromazine, as a single drug may be more effective than treatment with morphine. 136 Infants treated with oral morphine had significantly longer median durations of treatment and hospitalization in comparison with infants treated with chlorpromazine.…”
Section: 119-121mentioning
confidence: 99%
“…No largescale studies have proven the efficacy of clonidine for NAS. 153,154 Clonidine and phenobarbital levels can be monitored, and both are beneficial for decreasing the duration of treatment as well as for curtailing the use of higher doses of morphine or methadone. 138,155 …”
Section: Pharmacological Carementioning
confidence: 99%
“…25,26,45 Clonidine as adjunctive therapy for NAS was associated with a decrease in the number of morphine doses, duration of treatment, or length of hospital stay. 25,45 From a recent randomized trial, clonidine given with morphine resulted in a shorter duration of therapy compared with the morphine and phenobarbital combination.…”
Section: Discussionmentioning
confidence: 99%
“…23,24 Recent studies found that clonidine was an effective adjunctive treatment when given with morphine or chloral hydrate. 25,26 Because of potential deleterious effects of continued postnatal opiate administration on the developing brain, 27 we evaluated the use of clonidine in the treatment of infants with NAS. We tested the hypothesis that clonidine would be better than morphine as a single-drug therapy for NAS as evidenced by improvement in neurobehavior and duration of treatment.…”
Section: What's Known On This Subjectmentioning
confidence: 99%